Analytic model of the remobilization of pinned glide dislocations: Including dislocation drag from phonon wind. (August 2020) - Blaschke, Daniel N.; Hunter, Abigail; Preston, Dean L.
Abstract: In this paper we discuss the effect of a non-constant dislocation drag coefficient on the very high strain rate regime within an analytic model describing mobile-immobile dislocation intersections applicable to fcc polycrystals. Based on previous work on dislocation drag, we estimate its temperature and pressure dependence and its effects on stress–strain rate relations. In the high temperature regime, we show that drag can remain the dominating effect even down to intermediate strain rates. We also discuss the consequences of having a limiting dislocation velocity, a feature which is typically predicted by analytic models of dislocation drag, but which is somewhat under debate because a number of MD simulations predict supersonic dislocations. Highlights: We discuss the effect of non-constant dislocation drag on very high strain rates. We do so within an analytic model of dislocation intersections for polycrystals. At high temperatures, drag can dominate even down to intermediate strain rates. We also discuss the consequences of having a limiting dislocation velocity.